Self-pollination versus cross-pollination of six self-compatible almond cultivars: Pollen tube growth and fruit set - Dicenta F.; Ortega E.; Cánovas J.A.; Egea J. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
The behaviour of six self-compatible almond cultivars after self- or cross-pollination was studied. Four cultivars were selections obtained at CEBAS (S2332, S4017, Antoñeta and Marta) and the other two were Guara and Lauranne. Fruit set was determined in the field after open-pollination, self-pollination by hand, self-pollination by bagging the branches showing flower buds, and cross pollination (both with a self-compatible and with a self-incompatible cultivar). Assays were also performed in the laboratory. The growth of the pollen tube after 24, 48, 72 and 96 hours was studied after self-pollination or cross-pollination. The results obtained showed no differences between self-pollination or cross-pollination regarding pollen tube growth or fruit set, which indicates the real possibility of cultivating monovarietal orchards of self-compatible cultivars.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)